2009
DOI: 10.1007/bf03191156
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of statistical power function for various diclofenac bioequivalence trials with different subject numbers

Abstract: This study presents application of statistical power function for the t-test and ANOVA F-test on the evaluation of diclofenac bioequivalence in trials with the wide variations in sample sizes (N = 12, 18 and 24). The power function, together with appropriate equations tables and figures, is used to calculate the power of the ANOVA for crossover design, the number of subjects for a given value of power and the minimum detectable difference in treatment means for different pharmacokinetic parameters of the formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…On the other hand, the simulated profile for DS2 diverged from the mean in vivo profile obtained in the study of Rao et al (2001). The observed shift of C max to higher values has indeed been noticed in some clinical trials with diclofenac SR tablets, including the already mentioned study that involved DS2 tablets (Suleiman et al 1989;Popović et al 2009). But, the simulated profile for DS2 with relatively sharp decrease in drug plasma concentration (Figure 4) indicate that drug therapeutic effect might not last as long as expected for SR tablet formulation.…”
Section: Drug-specific Pbpk Modelssupporting
confidence: 65%
See 2 more Smart Citations
“…On the other hand, the simulated profile for DS2 diverged from the mean in vivo profile obtained in the study of Rao et al (2001). The observed shift of C max to higher values has indeed been noticed in some clinical trials with diclofenac SR tablets, including the already mentioned study that involved DS2 tablets (Suleiman et al 1989;Popović et al 2009). But, the simulated profile for DS2 with relatively sharp decrease in drug plasma concentration (Figure 4) indicate that drug therapeutic effect might not last as long as expected for SR tablet formulation.…”
Section: Drug-specific Pbpk Modelssupporting
confidence: 65%
“…Although the selected in vitro data indicated notable differences in the rate of drug release from the two formulations, several arguments supported the assumption that this scenario might actually happen in vivo. Namely, the results from BE study with DS2 tablets (Popović et al 2009) indicated considerably higher C max and AUC in comparison to the average values observed for 100 mg DS SR tablets (Davies & Anderson 1997), and in addition several trials showed that pharmacokinetics of orally taken diclofenac are highly variable (Hooper et al 1996;Lötsch et al 2000;Garbacz et al 2008).…”
Section: Drug-specific Pbpk Modelsmentioning
confidence: 96%
See 1 more Smart Citation
“…Determining a correlation between in vitro physical and release properties, and in vivo bioavailability profile of a drug has widely been presented in the bibliography studeis. 1,2 Assuming correlation, it is possible to use in vitro data to predict the behavior of the drug in the in vivo conditions. This is anticipated to significantly lower need for expensive bioequivalence evaluations in humans.…”
Section: Introductionmentioning
confidence: 99%